LAW ENFORCEMENT AGAINST REFUGEES WHO VIOLATE THE RULES IN PEKANBARU CITY BASED ON PRESIDENTIAL REGULATION NUMBER 125 OF 2016 CONCERNING HANDLING OF REFUGEES FROM ABROAD - Fahli, Zul; Triana, Yeni; Harahap, Irawan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
ABSTRACT Article 30 paragraph (2) of Presidential Regulation Number 125 of 2016 concerning Handling of Refugees from Abroad regulates sanctions for special placement/isolation of refugees who violate accommodation regulations.